Analysis Relationship of Economic Growth, Fiscal Policies and Demographic to Islamic Human Development Index in Indonesia (Granger Causality Approach) - Rukiah Lubis (IAIN Padangsidimpuan, 2020)
The purpose of study is to analyze the relationship of Economic Growth, Fiscal Policies, and Demographic to Islamic Human Development Index in Indonesia. The analysis method used Granger Causality test in 33 representative provinces. Taked sampling with Criteria Purporsive Sampling method. The results showed that there was relationship between Economic growth to Demographic and Islamic Human Development Index. There was relationship between Demographic to IHDI and fiscal policy in health and education. There was relationship of Fiscal Policy in health to Fiscal Policy in education. Recommendation of study was 1. Increasing economic growth with equity to support the maximalization IHDI in each region. 2. Optimizing Fiscal policies performance to improving public services in education and health so can be impact on the high IHDI distributed in Indonesia.